Residual disease after neoadjuvant chemoradiotherapy for oesophageal cancer: locations undetected by endoscopic biopsies in the preSANO trial. Issue 13 (5th August 2020) - van der Wilk, B. J.; Eyck, B. M.; Doukas, M.; Spaander, M. C. W.; Schoon, E. J.; Krishnadath, K. K.; Oostenbrug, L. E.; Lagarde, S. M.; Wijnhoven, B. P. L.; Looijenga, L. H. J.; Biermann, K.; van Lanschot, J. J. B.
Abstract : Background: Active surveillance has been proposed for patients with oesophageal cancer in whom there is a complete clinical response after neoadjuvant chemoradiotherapy (nCRT). However, endoscopic biopsies have limited negative predictive value in detecting residual disease. This study determined the location of residual tumour following surgery to improve surveillance and endoscopic strategies. Methods: The present study was based on patients who participated in the prospective preSANO trial with adenocarcinoma or squamous cell carcinoma of the oesophagus or oesophagogastric junction treated in four Dutch hospitals between 2013 and 2016. Resection specimens and endoscopic biopsies taken during clinical response evaluations after nCRT were reviewed by two expert gastrointestinal pathologists. The exact location of residual disease in the oesophageal wall was determined in resection specimens. Endoscopic biopsies were assessed for the presence of structures representing the submucosal layer of the oesophageal wall. Results: In total, 119 eligible patients underwent clinical response evaluations after nCRT followed by standard surgery. Residual tumour was present in endoscopic biopsies from 70 patients, confirmed on histological analysis of the resected organ. Residual tumour was present in the resection specimen from 27 of the other 49 patients, despite endoscopic biopsies being negative. Of these 27 patients, residual tumour was located in the mucosa in 18, and in the submucosa beneath tumour‐free mucosa in eight. One patient had tumour in muscle beneath tumour‐free mucosa and submucosa. Conclusion: Most residual disease after nCRT missed by endoscopic biopsies was located in the mucosa. Active surveillance could be improved by more sampling and considering submucosal biopsies. Abstract : Remnant cancer missed by endoscopic biopsies was located in the mucosa in two‐thirds of patients with residual disease after neoadjuvant chemoradiotherapy (nCRT). One‐third of patients had residual disease in the submucosa underneath a tumour‐free mucosa. The yield of biopsies in active surveillance after nCRT could be improved by sampling larger areas of oesophageal mucosa and using biopsies targeting the submucosa. What lies beneath Abstract : Antecedentes: Se ha propuesto un seguimiento activo para los pacientes con cáncer de esófago en los que se logra una respuesta clínica completa tras quimiorradioterapia neoadyuvante ( neoadjuvant chemoradiotherapy, nCRT). Sin embargo, las biopsias endoscópicas tienen un valor predictivo limitado para detectar la enfermedad residual. En este estudio se evaluó la localización del tumor residual tras la cirugía para poder determinar estrategias de seguimiento y endoscópicas. Métodos: Este estudio se basa en pacientes que participaron en el ensayo prospectivo preSANO (adenocarcinoma o carcinoma escamoso del esófago o unión esofagogástrica en cuatro hospitales de los Países Bajos entre 2013 y 2016). Los especímenes quirúrgicos, así como las biopsias endoscópicas efectuadas durante las evaluaciones de la respuesta clínica después de nCRT fueron revisadas por dos patólogos gastrointestinales expertos. En los especímenes de resección, se determinó la localización exacta de la enfermedad residual en la pared del esófago. Se evaluaron las biopsias endoscópicas para identificar estructuras que constituyeran la capa submucosa de la pared del esófago. Resultados: En total, 119 pacientes elegibles fueron sometidos a evaluaciones de la respuesta clínica tras nCRT seguida de cirugía estándar. Se detectó tumor residual en las biopsias endoscópicas de 70 pacientes, luego confirmadas en la histología de la pieza extirpada. Se identificó tumor residual en la pieza de resección de 27 de los otros 49 pacientes, a pesar de que las biopsias endoscópicas fueron negativas. En estos 27 pacientes, 18 presentaban tumor residual en la mucosa y ocho pacientes en la submucosa mas allá de una mucosa libre de tumor. Un paciente tenía tumor en el músculo más allá de una mucosa y submucosa libres de tumor. Conclusión: La mayoría de los casos de enfermedad residual tras nCRT que no se detectaron en las biopsias endoscópicas, se localizaban en la mucosa. El seguimiento activo podría mejorar con la toma de más muestras y considerando las biopsias submucosas.